Gender Analysis of Understanding the Tax Harmonization Law and Government Treasurer Competence in Tax Compliance (Case Study at the Education Standards, Curriculum, and Assessment Agency) - PALUPI, Retno; HIDAYAH, Nurul (PT Keberlanjutan Strategis Indonesia, 2025)
The purpose of this study is to examine and analyze the understanding of the tax regulation harmonization law and the competence of government treasurers towards tax compliance from the perspective of male and female genders. Tax compliance research is often conducted on MSMEs; the author chose government treasurers as a novelty from previous studies. The population of this study was government treasurers at the Education Standards, Curriculum and Assessment Agency. The data collection method was carried out by distributing questionnaires to taxpayer treasurers. The data processing technique used was Structural Equation Modeling (SEM) with SmartPLS 3.0 software. The results of the study indicate that 1) Understanding of knowledge of the HPP Law (male gender) has a positive effect on tax compliance. 2) Understanding of knowledge of the HPP Law (female gender) has a positive effect on tax compliance. 3) Competence of government treasurers (male gender) has a positive and significant effect on treasurer tax compliance. 4) Competence of government treasurers (female gender) has a positive and significant effect on treasurer tax compliance. This study is expected to be used as a reference for further research and provide input for the government in order to create policies related to tax regulations to facilitate government treasurers in carrying out their tax obligations.